PENGARUH DIMENSI BAURAN PEMASARAN TERHADAP KEPUTUSAN SISWA MEMILIH BIDANG KEAHLIAN BISNIS DAN MANAJEMEN DI SMK NEGERI 1 MALANG - Nurhayati (Institute Agama Islam Al-Qolam Malang, 2020)
The marketing mix is ??a marketing tool that can be controlled and used by the company to produce the desired response from the market, both trading companies and service companies. The marketing mix is ??important to do before recruiting new students. Vocational High School (SMK) continues to develop in the present with various fields of expertise offered. This of course requires creativity and competency expertise in each SMK to attract students to choose certain areas of expertise. The challenge of SMKN 1 Malang to attract students' interest, especially students who want and are interested in studying management sciences, is required to choose a relevant form of marketing. The marketing strategy that is carried out must achieve the target of vocational education institutions, which can be in the form of the number of student acquisition that corresponds to the number of study groups, certain market shares and the growing development of educational institutions and marketing policies must be in line with emphasizing providing beneficial services to consumers. This study aims to: (1) describe the marketing mix of students' decisions to choose Business and Management schools at SMKN 1 Malang. (2) Analyzing the influence of the dimensions of the marketing mix (product, price, place, promotion, people, process, physical evidence) on the student's decision to choose a School of Business and Management at SMKN 1 Malang. (3) To analyze the marketing mix variables that have a dominant influence on students' decisions to choose Business and Management schools at SMKN 1 Malang. This research is a quantitative descriptive study using multiple linear regression equation analysis techniques, in this study there are two types of variables, namely (1) independent variables consisting of: product (X1), price (X2), place (X3), promotion (X4) , people (X5), process (X6), and physical facilities (X7); (2) the dependent variable is Student Decision (Y). The population in this study were all students of SMKN 1 Malang who chose the Field of Business and Management Expertise for the 2013/2014 academic year as many as 1,332 students, the sample was taken as many as 93 students with the sampling technique using Proportioned Stratified Random Sampling. This study uses instruments in the form of a questionnaire and documentation with a Likert scale 5 Options, which consists of the options Strongly Disagree (1), Disagree (2), Disagree (3), Agree (4), and Strongly Agree (5).